ASSESSING THE INFLUENCE OF FINANCIAL INCLUSION AND DIGITAL FINANCE ON SMES PERFORMANCE: THE MODERATING ROLE OF TECHNOLOGICAL ADAPTATION - Muhammad Zulqarnain; Muhammad Mustehsan; Usman Khan Balouch; Samavia Munir (Universitas Nusa Cendana, 2023)
The study's overarching goal is to shed light on the connections between technical progress, the success of Pakistani SMEs, and broadening access to financial services. The survey was administered to 212 different SMEs through an online system. Experts in various fields will be selected at random. Statistical tools such as correlation tests, reliability analyses, regression analyses, and moderation analyses will be utilized to investigate the information gathered. Having many financial options available to them increases the likelihood of success for small and medium-sized businesses (also known as SMEs). The favorable correlation between digital finance and productivity, financial inclusion, and economic development was tempered by the degree to which small and medium-sized firms were receptive to embracing new technology. Financial inclusion and digital banking are more beneficial to technologically innovative SMEs than to less adaptable rivals. This is because SMEs are the most open to using cutting-edge tools. Based on our findings, we conclude that politicians and financial institutions need to advocate for increased financial inclusion and digital banking, while small and medium-sized businesses (SMEs) should emphasize technological adaptation. Keywords: Financial Inclusion; Digital Finance; Technological adaptation; SMEs Performance